Optimizing fish structure in angling ponds focusing on white fish - Molnár, József; Csorbai, Balázs; Bernáth, Gergely; Várkonyi, Levente; Urbányi, Béla; Bokor, Zoltán (Acta Agraria Debreceniensis, 2019)
According to new amendments of laws, commercial fishing licenses of natural waters shall not be issued from the calendar year 2016 in Hungary. However, the most settlement of white fish to angler ponds originated from natural waters. Currently, there is no sufficient quantity of fish species belonging to this group available to fulfil the settlement commitments of fish farmers. The aim of this recent study is to develop a breeding and production technology that is suitable for settlement of large quantities of this fish species of appropriate length of (4–5 cm). The following methods are investigated: aquaculture cage system (pond-in-pond system), monoculture and mixed population with different ratio of white fish in fish structure. Due to the different environmental needs of different fish species, many parameters need to be investigated, for example: stocking density, feeding, oxygen level, monoculture or mixed populations, growth potential and mortality. A preliminary experiment was carried out following the artificial propagation of ide (Leuciscus idus) following a 21-day larval rearing experiment in which the effect of different stoking density was investigated for mortality and growth. On the basis of the expected results, the optimal conditions for the aquaculture cage system will be described, regarding to the white fish stock.